Research on the influence of cultural distance on export of traditional Chinese medicine products - based on the empirical analysis of countries along the belt and road - Wang, Zhengwei; Leng, Youxu (Edelweiss Applied Science and Technology, 2025)
In this era, when people are increasingly concerned about health, traditional Chinese medicine, with its unique theories and rich practical experience, has gradually increased its influence in the global health field. Against this background, this article focuses on conducting an in-depth exploration of the influencing factors of cultural distance on the trade of traditional Chinese medicine products between China and the countries along the "Belt and Road." Cultural differences (CD) have had a significant negative impact on the trade volume of traditional Chinese medicine products. That is to say, the greater the degree of cultural differences, the lower the trade volume of traditional Chinese medicine products. This fully indicates that cultural differences have formed certain obstacles in the trade of traditional Chinese medicine. Among the numerous control variables, gross domestic product (GDP) and per capita gross national income (GNI) of trading countries show a positive correlation with the volume of trade. This implies that sustained economic development and the relatively high income level of residents in these countries can effectively promote the import of traditional Chinese medicine products. Conversely, geographical distance (DIS) has brought negative effects to trade. Due to increased distance, trade costs rise, which in turn suppresses the export of traditional Chinese medicine products. Furthermore, common language (LAN) and population size (POP) have also played a promoting role in trade, with the role of common language being more crucial. Although the effect of free trade agreements (FTAs) in promoting trade is not yet fully clear at present, judging from the relatively large coefficient values, they have the potential to drive trade growth. To further analyze the influence mechanism of cultural factors in trade, a mechanism test was carried out in the research. The results show that the Power Distance Index (PDI) presents a significant positive correlation with trade volume. The Individualism and Collectivism Index (IDV), the Uncertainty Avoidance Index (UAI), and the Indulgence and Restraint Index (IVR) are all significantly negatively correlated with trade volume. The long-term orientation (LTO) is significantly positively correlated with the short-term normative orientation and trade volume. However, the dimensions of masculinity and femininity (MAS) have no obvious influence on trade volume. Through heterogeneity analysis, it was found that cultural differences have a more prominent inhibitory effect on the trade of traditional Chinese medicine in non-high-income countries. High-income countries, relying on their own advantages and with the assistance of economic factors that promote trade and a common language, can obtain more trade dividends. Meanwhile, geographical distance poses a more serious trade obstacle for non-high-income countries. These research results comprehensively and deeply reveal the intricate relationship between cultural distance and the trade of traditional Chinese medicine.